TINJAUAN YURIDIS UNDANG-UNDANG APARATUR SIPIL NEGARA DALAM PEMENUHAN HAK DISABILITAS SEBAGAI PEGAWAI NEGERI SIPIL - Bayyinati Janah, - (2021)
The purpose of this paper is to find out how the implementation of the fulfillment of human rights for people with disabilities who want to become Civil Servants and aims as a form of contribution to the issue of disability law in the legal and regulatory aspects, in which this study discusses the protection of the rights of persons with disabilities as civil servants. civil servants and the legal consequences of discrimination in the fulfillment of civil servant rights for persons with disabilities. Seeing the frequent occurrence of acts of discrimination, one of which is discrimination experienced by Alde Maulana, Alde Maulana failed to be appointed as a civil servant and was dismissed as a civil servant candidate for reasons of health or disability, this is an example that the implementation of legal protection for persons with disabilities by the government is not optimal in providing justice and facilities that are not in accordance with the applicable laws and regulations. The research method in this paper uses a normative juridical approach to legislation. The conclusion of this paper is that in writing all persons with disabilities have been protected by law both in the ASN Law, the 1945 Constitution and the Disability Law, but in the implementation all these rules are still not implemented properly and perfectly in their health qualifications in the procurement of Civil Servant Candidates.